2020
DOI: 10.1111/1467-8489.12392
|View full text |Cite
|
Sign up to set email alerts
|

Cycles in cattle and hog prices in South America

Abstract: Prices of agricultural products often vary in relatively stable patterns around their long-run trends. These variations translate into fluctuations of selling prices as well as farm revenues. We provide an overview of the current literature on agricultural price cycles. Using a transparent and reproducible model selection process and the Kalman filter, we select optimal models and estimate the cyclic patterns of hog and cattle prices for Brazil, Chile and Uruguay. Durations of those cycles are found to be abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…However, these previous findings did not agree with those of this analysis as they were based on qualitative not quantitative statistical analysis. Another study that was conducted using data from three different countries in South America that include Brazil Chile, and Uruguay indicated that the cattle price cycle was about seven years, which falls within the same range of the identified cycle in this study [43]. The obtained cycles are in agreement with the biological aspects of beef cattle production system as the cow-calf production systems can experience long production time lags [44], due to the fact of the nine months of gestation and another six to nine months are needed until calves are ready to be sold.…”
Section: Production and Drought Cyclessupporting
confidence: 76%
“…However, these previous findings did not agree with those of this analysis as they were based on qualitative not quantitative statistical analysis. Another study that was conducted using data from three different countries in South America that include Brazil Chile, and Uruguay indicated that the cattle price cycle was about seven years, which falls within the same range of the identified cycle in this study [43]. The obtained cycles are in agreement with the biological aspects of beef cattle production system as the cow-calf production systems can experience long production time lags [44], due to the fact of the nine months of gestation and another six to nine months are needed until calves are ready to be sold.…”
Section: Production and Drought Cyclessupporting
confidence: 76%
“…This influences the smaller number of animals for replacement and finishing, being noticed after two or three years with the increase in prices. Given the increase in prices, cattle raisers tend to retain matrices for the production of calves with a long-term supply of fattened cattle, thus restarting a new livestock cycle [20].…”
Section: Price Behaviormentioning
confidence: 99%
“…The applications of unobserved-component models provide useful descriptions of price cycles. But, as noted in Fliessbach and Ihle (2020), the resulting statistical decompositions are not based on theoretical models of agricultural price fluctuations and hence cannot be construed as conclusive evidence of endogenous dynamics.…”
Section: Introductionmentioning
confidence: 98%
“…The co‐existence of high and low frequency cycles in commodity prices is well‐documented (Rossen, 2015). Following Fliessbach and Ihle (2020), we utilized unobserved‐component models to describe the main features of cycles in chick and broiler prices. We estimated different random‐walk and local‐level specifications with trend, drift, and seasonality components.…”
Section: Introductionmentioning
confidence: 99%